Pengaruh profitabilitas dan leverage terhadap tax avoidance pada perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Miranda, Putri Anisa; Mulyati, Yati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to find out how profitability and leverage affect tax avoidance in mining sector companies listed on the Indonesia Stock Exchange for the 2018–2020 period. The factors tested in this study are profitability and leverage as independent variables and tax avoidance as the dependent variable. The research method used in this study is the verification method. The population in this study is mining sector companies listed on the Indonesia Stock Exchange for the 2018–2020 period, which includes as many as 44 companies. The sampling technique used in this study is non-probability sampling with a purposive sampling method, so that the total sample is 18 companies. The data analysis used in this study was panel data regression analysis at a significance level of 5% using the Eviews 10 program. The results showed that profitability and leverage had an effect on tax avoidance. In addition, the influence of profitability and leverage in contributing to tax avoidance is 51.1%.